Daylight adaptive optimal lighting system control strategies for energy savings and visual comfort in commercial buildings - Wagiman, Khairul Rijal (2020)
Artificial lighting of commercial buildings in Malaysia consumes 21% of the total electrical energy. Therefore, reducing the energy is required to achieve sustainable buildings (i.e., higher energy efficiency and visual comfort), by implementing optimal light sensor placement method and optimisation-based control strategy. However, in recent works related to light sensor placement, energy performance and illuminance uniformity (Uo) are not considered, and the results did not provide the optimal number of sensors to be employed. To optimise power consumption (PC) and visual comfort simultaneously through the optimisation-based control strategy, the previous work developed a visual comfort model to represent Uo. However, the model did not consider daylight and the results of Uo need further improvement. This research proposes: (1) a new optimal light sensor placement method (OLSPM) by using combined particle swarm optimisation (PSO) and fuzzy logic controller (FLC) denoted as OLSPM-PSOFLC, and (2) a new visual comfort metric called illuminance uniformity deviation index (IUDI) and incorporated with multi-objective PSO (MOPSO) for solving energy consumption and visual comfort problem. The OLSPMPSOFLC is developed to determine the optimal number and position of light sensors by considering PC while satisfying average illuminance level (Eav) and Uo. To ensure both PC and Uo in the room are always at the optimum levels, the IUDI with MOPSO is developed. Before the proposed methods are implemented, retrofitting lighting system is implemented first to determine the best lamp technology to be installed in terms of technical and economic metrics. An actual office room is considered for carrying out the proposed methods. The comparative results showed that the OLSPMPSOFLC significantly reduced the number of sensors, energy consumption, carbon dioxide emission, payback period, and life cycle cost were 66%, 23%, 23%, and 30%, respectively, compared to the multi-sensor. Meanwhile, based on the comparative study of the IUDI and CVRMSE, the IUDI showed superior performance with 6% and 27% improvement of Uo and energy savings, respectively. Based on their superiority, the newly developed methods can be potentially implemented for all types of rooms and are very useful methodologies towards sustainable commercial buildings.